The Hamiltonian in the unidirectional surface wave propagation. Issue 1 (February 2021) - Fadhiliani, D; Qausar, H; Ramli, M; Rizal, S; Syafwan, M
Abstract: Unidirectional surface water waves used in this study were obtained from the Benjamin Bona Mahony (BBM) equation. The BBM wave research is carried out by observing the envelope of BBM wave groups that involve following the Nonlinear Schrodinger (NLS) Equation. Soliton on Finite Background (SFB) is an excellent NLS solution for describing the dynamics of wave propagation. It is known that there are modulation instability and phase singularity phenomena which can significantly affect the amplitude of the wave in its propagation. Hamiltonian contains potential energy which can explain the singularity and amplitude dynamics of the phase. Hamiltonian equations using the displaced phase-amplitude variables have been obtained and are presented in this article.